Application of Quality Costs on Activities Based and Their Impact on Cost Reduction / Applied Research in the General Company for Leather Industries - Atheer Ali Abdulkadhim; Khawla Hussein Hamdan (Journal of Madenat Alelem University College, 2021)
The objective of the research is to determine the indirect quality costs based on the activities according to its four components: prevention (prevention), evaluation, internal and external failure, as well as to demonstrate the impact of quality costs on activity basis in reducing costs. The problem of research was no interest in determing indirect quality cost on activity based and the extent to which they can be measured according to its four elements and its impact on the quality of the product. It will benefit from it, as well as the information it provides to management for the purpose of making decisions, as well as to several recommendations. Reducing the costs of both failures (internal and external).